Brain Metabolism During A Lower Extremity Voluntary Movement Task in Children With Spastic Cerebral Palsy - Fowler, Eileen G.; Oppenheim, William L.; Greenberg, Marcia B.; Staudt, Loretta A.; Joshi, Shantanu H.; Silverman, Daniel H. S. (Frontiers in Human Neuroscience, 2020)
Reduced selective voluntary motor control (SVMC) is a primary impairment due to corticospinal tract (CST) injury in spastic cerebral palsy (CP). There are few studies of brain metabolism in CP and none have examined brain metabolism during a motor task. Nine children with bilateral spastic CP (Age: 6-11 years, GMFCS Levels II – V) completed this study. SVMC was evaluated using Selective Control Assessment of the Lower Extremity (SCALE) ranging from 0 (absent) - 10 (normal). Brain metabolism was measured using PET scanning in association with a selective ankle motor task. Whole brain activation maps as well as ROI averaged metabolic activity were correlated with SCALE scores. The contralateral sensorimotor and superior parietal cortex were positively correlated with SCALE scores (p < 0.0005). In contrast, a negative correlation of metabolic activity with SCALE was found in the cerebellum (p < 0.0005). Both ipsilateral and contralateral cerebellar metabolism correlated with SCALE but the relationship for the ipsilateral cerebellum was stronger (R2 = 0.80, p < 0.001 versus R2 = 0.46, p = 0.045). Decreased cortical and increased cerebellar activation in children with less SVMC may be related to task difficulty, activation of new motor learning paradigms in the cerebellum and potential engagement of alternative motor systems when CSTs are focally damaged. These results support SCALE as a clinical correlate of neurological impairment.